2017
DOI: 10.1186/s12889-017-4262-3
|View full text |Cite
|
Sign up to set email alerts
|

Household food insecurity is associated with abdominal but not general obesity among Iranian children

Abstract: BackgroundChildhood obesity is increasing all over the world. Food insecurity is mentioned as a possible risk factor; however, previous studies have led to inconsistent results in different societies while data are lacking for the Middle East. We aimed to investigate the relationship between food insecurity and general or abdominal obesity in Iranian children in a cross-sectional study.MethodsAnthropometric data including height, weight, and waist circumference were measured by trained nutritionists. General a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
(35 reference statements)
0
12
1
Order By: Relevance
“…The study revealed that the Household Food Insecurity Access Scale is a valid tool for examining children's development in different geographical regions [ 26 ]. There has been evidence suggesting that obesity and overweight, which is considered a growing public health threat, particularly in low-income populations, is associated with food insecurity [ 27 28 29 30 ]. This association is sometimes in the form of obesity and overweight combined with stunting [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that the Household Food Insecurity Access Scale is a valid tool for examining children's development in different geographical regions [ 26 ]. There has been evidence suggesting that obesity and overweight, which is considered a growing public health threat, particularly in low-income populations, is associated with food insecurity [ 27 28 29 30 ]. This association is sometimes in the form of obesity and overweight combined with stunting [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 32 articles met the inclusion criteria to be included in the meta-analysis. [ 20 21 22 25 26 27 28 29 30 31 32 34 35 36 37 38 39 40 41 42 43 48 49 50 51 52 53 54 55 56 57 58 ] In these 32 articles, 26 used a cross-sectional setting,[ 20 21 22 27 29 30 31 32 33 35 36 38 39 40 41 42 43 48 50 51 52 53 54 55 56 57 58 ] whereas the other 6 were longitudinal studies. [ 25 26 28 34 37 49 ] The OR of 139.762 participants was analyzed among these articles for the present study.…”
Section: Resultsmentioning
confidence: 99%
“…[ 25 26 28 34 37 49 ] The OR of 139.762 participants was analyzed among these articles for the present study. These articles were published during 2001 and 2019, and performed in the Canada,[ 22 25 27 ] United States,[ 20 21 26 28 29 30 32 34 36 37 38 39 40 42 49 50 52 55 56 57 58 ] Jamaica[ 27 ] Brazil,[ 41 48 ] Mexico,[ 26 31 51 ] Colombia,[ 35 ] Iran[ 43 54 ] and Taiwan. [ 53 ] Table 1 showed the feature of the articles included.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations